THE IMPACT OF RENEWABLE ENERGY USE ON BIODIVERSITY - Irwanto, Miko Mei; Nampira, Ardi Azhar (PT. Hafasy Dwi Nawasena, 2025)
The global shift toward renewable energy is a crucial response to the climate crisis, yet it also brings ecological implications that are often overlooked. This study systematically examines the environmental impact of renewable energy infrastructures particularly solar, wind, hydro, and biomass on terrestrial and aquatic biodiversity. A total of ten peer-reviewed articles published between 2020 and 2025 were selected based on their relevance, methodological rigor, and ecological focus. The data were analyzed using a narrative-descriptive approach supported by manual thematic coding to identify recurring ecological patterns and mitigation strategies. The results indicate that solar farms contribute to habitat fragmentation and behavioral disturbances among birds and bats; wind turbines are linked to elevated mortality in flying species; and hydroelectric dams disrupt fish migration and reduce aquatic habitat quality. On the other hand, integrative technologies such as aquavoltaic systems and fish-friendly turbines demonstrate potential for minimizing ecological harm while meeting energy needs. This study contributes a synthesized understanding of how renewable energy infrastructures affect biodiversity across ecosystems and technological contexts. It highlights the importance of spatial planning, context-specific impact assessments, and ecosystem-based mitigation strategies. The findings are expected to inform policymakers, environmental planners, and industry stakeholders in designing renewable energy solutions that align with long-term ecological sustainability.